Life Goes On: An Exploration into the Experience of Community Reintegration for Working-aged Persons Post-Stroke - Fleck, Rebecca J. (My University, 2014)
Since 2004, there has been a 12% relative increase in stroke prevalence in the working-aged (18–65 years) population of Ontario. Studies have shown that successful community reintegration is an important indicator of perceived quality of life post-stroke.
The purpose of this interpretive phenomenological study was to explore the lived experience of community reintegration for working-aged persons post-stroke in order to inform the development of appropriate and effective strategies to support their community reintegration and continued stroke recovery.
The essence of the phenomenon of community reintegration for working-aged persons post-stroke emerged as: “Life Goes On: The journey of surviving a stroke in the prime of your life”. Six themes emerged to support this journey of community reintegration after stroke: 1) processing the shock, 2) starting the road to recovery, 3) living with stroke, 4) who am I? 5) carrying-on and 6) transcending the stroke. While participants experienced their personal journey to community reintegration in a unique way, their journey led them to realize that in order to successfully reintegrate back into their community, they needed to adjust, adapt and reach some level of acceptance in order to move on and essentially transcend their stroke
There needs to be a call to action for the delivery of client-centered stroke care. A client centered approach to stroke care will ensure that the voices of working-aged persons post-stroke are heard and given priority in their rehabilitation and community reintegration planning.
Keywords: Stroke; Community Reintegration; Working-aged; Qualitative; Rehabilitation and Therapy; Rehabilitation and Therapy